Mouse and keyboard control by Kinect - Sawanglok, Tanakon (Science Technology and Innovation Journal, 2020)
Mouse and keyboard control by Kinect is a system that uses body movement as a system controller (Motion controller) via Kinect device. In this system, the physicians are not required to use keyboards and mouse to operate. This aims to solve two problems: Communication problem and misunderstanding between physicians and assistants, and The surgeon need to use approximately 20 minutes in cleaning their hands when they need to use computers.